Early intervention for children with autism: An Australian rural hub and spokes model. Issue 1 (2nd January 2016) - Stephens, Miranda; Allen, Penny; Fordyce, Kathryn; Minchin, Alice; Cheek, Colleen
ABSTRACT: The North West Tasmania Autism Specific Early Learning and Care Centre offers early intervention to children with autism symptoms in an extended hours Child Care Centre. In this regional and rural area it operates as a hub and spokes model with children from outlying areas receiving intervention from educators at their local mainstream childcare centre supported by specialist staff at the North West Tasmania Autism Specific Early Learning and Care Centre. We analysed clinical assessments of all children over the period 2009–2014 at entry and follow-up and found children in the spokes centres were achieving similar outcomes to those in the hub centres. The outcomes appeared to be moderated by the limited attendance of children with a smaller effect sizes on the majority of measures compared to best practice. However, larger effect sizes on the measure of socialisation could reflect the emphasis of the program on the social skills needed for participation in mainstream school environments.